La ciencia política como disciplina universitaria en Colombia - Duque Daza, Javier (Universidad Icesi, 2014)
This paper analyzes the current state of political science as an academic discipline in Colombia. Considering the concept of institutionalization as a departure point, the author examines five discipline components, namely, the development of teaching, educators, research, publications, and the recent emergence of a profession association as well as the implementation of the first national congress. The author identifies strengths and weaknesses of the Colombia’s recent institutionalization process and shows that the process has been uneven with regard to different Colombian universities. As it turned out, in Colombia, political science is a discipline developed primarily at private institutions, with a limited admission rates but with high concentration of research, doctoral training, and the number of academic publications.
Este artículo analiza el estado actual de la ciencia política como disciplina universitaria en Colombia. A partir del concepto de institucionalización presenta una visión de conjunto de cinco componentes de la disciplina: la expansión de la docencia, los profesores, la investigación, las publicaciones y el reciente proceso de surgimiento de agremiaciones y realización de los primeros congresos nacionales. El argumento central es que Colombia presenta un proceso de institucionalización reciente, con fortalezas y debilidades y un desarrollo desigual entre universidades. Se trata de una disciplina desarrollada especialmente en instituciones privadas y con limitaciones de acceso y alta concentración de la investigación, la formación doctoral y las publicaciones consolidadas.
Keywords: Producción intelectual registrada - Universidad Icesi; Ciencia política; Institucionalización; Disciplina; Political Science; Politólogos; Institutionalization; Discipline; University; Political scientists